Pengaruh Profitabilitas, Likuiditas, Leverage dan Kepemilikan Manajerial Terhadap Nilai Perusahaan - Yuna Oktawida; Suyatmin Waskito Adi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Firm value measures the amount of a company's stock market price against its book value as an illustration of investors' perceptions of their confidence in the company for good performance prospects in the future. This study aims to analyze the effect of profitability, liquidity, leverage, and managerial ownership on firm value in manufacture companies on the Indonesia Stock Exchange for the period 2020–2022. The sampling technique used in this study was purposive sampling. This research sample consists of 46 companies that meet the criteria as a unit of analysis. The results provide empirical evidence that profitability has effect firm value, Meanwhile liquidity, leverage, and managerial ownership have no effect on firm value.